PENANGGULANGAN ORIENTASI LGBT PADA ANAK USIA BALIGH : (Kajian Psikologi dan Al-Quran) - Iin Yuniarni; Derysmono, Derysmono (el-Umdah, 2022)
The Citayam Fashion Week (CFW) event in July 2022, -led by amateur teenagers-, suddenly became virtual in cyberspace. The massive emergence of the lifetrend of young groups of lesbian, gay, bisexual and transgender or popularly referred to as LGBT on the event of CFW, rekindled diverse polemics in the social realities of society at large. Although since 2001 when the Netherlands first until now almost 30 other countries have consciously officially legalized the LGBT movement, the LGBT phenomenon which is categorized as a form of deviation of sexual orientation, in fact LGBT is still a long discourse and has not ended either among academics, practitioners or the wider community. The arguments are manifold; starting from the change in LGBT status from the master book of psychology (DSM) Diagnostic and Statistical Manual of Mental Disorder, namely from the category of sexual deviance orientation to the category of orientation that seems natural and commonplace, to the arguments of the Holy books including the Qur'an with postulates whose verses are clear and well established. This research applies an analytical descriptive qualitative methodology, based on the Qur'ani of psychology using nomatic techniques, to find prevention from the orientation of LGBT towards children at young age . The results reveal the phenomenon of LGBT psychiatry and the impact of LGBT life trends on “baligh” age in the contemporary digital age. This study offers 4 continuums of the Qur'ani cognitive adjustment models, namely: 1. To strengthen moral education and applied theory of cognition husn al-Zahn/positive attribution, 2. To strengthen family resilience, 3. To choose a good social environment, 4. To synergy between the government, the legislator and the formation of law against LGBT.